All‐Level Versus Alternative‐Level in Unilateral Laminoplasty: A Retrospective Comparative Study - Bin Zheng; Zhenqi Zhu; Yan Liang; Haiying Liu (Orthopaedic Surgery, 2025)
ABSTRACT Objective Titanium mini‐plates are applied in unilateral open‐door laminoplasty to secure the elevated laminae and prevent re‐closure. Whereas the conventional technique fixates every level, some surgeons plate only alternate levels to curb implant costs. Whether they could achieve similar long‐term clinical and radiographic efficacy is still questionable. This study aimed to compare the efficacy and safety of alternative‐level fixation versus all‐level fixation in cervical laminoplasty for multilevel cervical spondylotic myelopathy (CSM). Methods A retrospective analysis is conducted on 65 patients who underwent C3–C7 unilateral laminoplasty at Peking University People's Hospital from July 2012 to December 2020. Patients are divided into two groups: alternative‐level fixation and all‐level fixation. Clinical outcomes, including operative time, intraoperative blood loss, postoperative hospitalization days, and complications, are assessed. The Japanese Orthopaedic Association (JOA) score is used for neurological function evaluation, while pain is assessed with the Visual Analog Scale (VAS). Radiographic outcomes include changes in anterior–posterior diameter, Pavlov ratio, cervical lordosis (CL), thoracic slope (T1S), and sagittal vertical axis (SVA). Results Both groups showed significant improvements in JOA (15.94 ± 0.85 vs. 8.74 ± 1.76 in alternative‐level and 16.1 ± 0.79 vs. 8.42 ± 1.84 in all‐level) and VAS (1.03 ± 0.87 vs. 5.79 ± 1.18 in alternative‐level, 1.06 ± 0.77 vs. 5.35 ± 1.17 in all‐level) postoperatively, with no statistically significant differences in clinical outcomes between the groups (JOA: 15.94 ± 0.85 vs. 16.1 ± 0.79, p = 0.394; VAS: 1.03 ± 0.87 vs. 1.06 ± 0.77, p = 0.432). Although total hospital costs are significantly lower in the alternative‐level fixation group (124,937 ± 5104.01 RMB vs. 88007.53 ± 7014.53, p < 0.001), the all‐level fixation group demonstrated better long‐term preservation of APD (17.87 ± 0.60 vs. 17.50 ± 0.52) at the final follow‐up. Radiographic outcomes, including CL, T1s, and cSVA, show no significant differences between the two groups, indicating comparable spinal alignment outcomes. Conclusion Both all‐level and alternative‐level fixation methods effectively support the lamina and prevent reclosure, with significant improvement in clinical symptoms in both groups at the final follow‐up, showing no significant difference in postoperative clinical outcomes between the two. There are no differences in sagittal parameters. All‐level fixation method showed better preservation of the spinal canal diameter.